Resin composition and peripheral sealant for organic EL display element
By using resin compositions such as polyisobutylene, curable resin and vapor phase silica in organic EL display elements, the poor display problem of existing sealant in high temperature and high humidity environments is solved, and excellent coating properties are achieved , adhesiveness and moisture-permeability significantly improve the stability and display performance of the components.
Patent Information
- Application Number
- CN202080009934.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-26
- Filing Date
- 2020-03-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-03-24
AI Technical Summary
The existing organic EL display elements have problems of poor display in high temperature and high humidity environments, and the existing sealant has insufficient moisture resistance and adhesiveness, which affects the stability and life of the components.
A resin composition is adopted, which contains polyisobutylene, a curable resin, a polymerization initiator and vapor phase silica. By adjusting its weight average molecular weight and component ratio, the coating, adhesiveness and moisture-permeability of the resin composition are improved. , an excellent peripheral sealant for organic EL display element is formed.
It achieves excellent adhesion and moisture resistance in high temperature and high humidity environments, significantly improves the display performance and stability of organic EL display elements, and extends the service life of the components.
Smart Images

Figure BDA0003169387600000201 
Figure BDA0003169387600000211
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition having excellent coating properties, adhesiveness and moisture permeation resistance, and capable of obtaining an organic EL display element having excellent display performance by being used in a peripheral sealant for an organic EL display element. In addition, the present invention relates to a peripheral sealant for an organic EL display element using the resin composition. Background Art
[0002] An organic electroluminescent display element (organic EL display element) has a thin film structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. Electrons are injected into the organic light-emitting material layer from one electrode, and holes are injected from the other electrode, so that electrons and holes combine in the organic light-emitting material layer to emit light. Compared with liquid crystal display elements that require a backlight, it has the advantages of good visual recognition, further thinning, and DC low voltage drive.
[0003] However, such organic EL display elements have the following problems: if the organic light-emitting material layer and the electrode are exposed to the outside air, the light-emitting characteristics thereof will be rapidly deteriorated and the life span will be shortened. Therefore, in order to improve the stability and durability of the organic EL display element, a sealing technology for isolating the organic light-emitting material layer and the electrode from moisture and oxygen in the atmosphere has become indispensable in the organic EL display element.
[0004] Patent document 1 discloses a method for sealing an organic EL display element by having a structure having an organic filling layer and a hygroscopic sealing layer (sealing wall), wherein the organic filling layer covers and seals a laminate having an organic light-emitting material layer, and the hygroscopic sealing layer covers the side of the organic filling layer. Usually, as a sealant for an organic EL display element, an in-plane sealant is used for the organic filling layer, and a peripheral sealant having a constituent component different from that of the in-plane sealant is used for the sealing wall. However, even when the organic EL display element is sealed using such an in-plane sealant and a peripheral sealant, there is sometimes a problem that the organic EL display element has a poor display when exposed to a harsh high temperature and high humidity environment.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-67598 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The object of the present invention is to provide a resin composition having excellent coating properties, adhesion properties and moisture permeability resistance, and being able to obtain an organic EL display element having excellent display performance by being used as a peripheral sealant for an organic EL display element. In addition, the object of the present invention is to provide a peripheral sealant for an organic EL display element formed by using the resin composition.
[0010] Means for solving problems
[0011] The present invention is a resin composition, which contains polyisobutylene, a curable resin, a polymerization initiator and fumed silica, wherein the weight average molecular weight of the polyisobutylene is greater than or equal to 5,000 and less than or equal to 100,000, the curable resin contains urethane (meth) acrylate, the content of the urethane (meth) acrylate is greater than or equal to 1 part by weight and less than or equal to 30 parts by weight relative to 100 parts by weight of the polyisobutylene, and the content of the fumed silica is greater than or equal to 1 part by weight and less than or equal to 30 parts by weight relative to 100 parts by weight of the polyisobutylene.
[0012] Hereinafter, the present invention will be described in detail.
[0013] The inventors of the present invention have studied the addition of polyisobutylene in order to improve the moisture-proof property of a resin composition used as a peripheral sealant for an organic EL display element. However, the resin composition obtained sometimes produces dripping (Japanese: liquid ダレ) during coating. Therefore, in order to prevent dripping during coating, the inventors of the present invention have studied the addition of fumed silica to the resin composition. However, in the case of a large amount of fumed silica being added in order to fully prevent dripping during coating, the adhesion and moisture-proof property of the resin composition obtained after exposure to a high temperature and high humidity environment sometimes deteriorate. Therefore, the inventors of the present invention have studied the addition of urethane (meth) acrylate and fumed silica in a manner that reaches a specific content ratio relative to polyisobutylene. As a result, it was found that: excellent coating property, adhesion (including adhesion after exposure to a high temperature and high humidity environment) and moisture-proof property can be obtained, and a resin composition of an organic EL display element with excellent display performance can be obtained by using it as a peripheral sealant for an organic EL display element, thereby completing the present invention.
[0014] It should be noted that, in this specification, the above-mentioned "(meth)acrylate" refers to acrylate or methacrylate, and the above-mentioned "urethane (meth)acrylate" refers to a compound having a urethane bond and a (meth)acryloyl group. In addition, the above-mentioned "(meth)acryloyl group" refers to an acryloyl group or a methacryloyl group.
[0015] The resin composition of the present invention contains polyisobutylene.
[0016] By containing the polyisobutylene, the resin composition of the present invention has excellent moisture permeation prevention properties and is less likely to be compatible with an in-plane sealant when used as a peripheral sealant for an organic EL display element.
[0017] The lower limit of the weight average molecular weight of the polyisobutylene is 5000, and the upper limit is 100,000. By setting the weight average molecular weight of the polyisobutylene to be within this range, the obtained resin composition has excellent coating properties, adhesion and moisture permeability. The preferred lower limit of the weight average molecular weight of the polyisobutylene is 20,000, the preferred upper limit is 80,000, the more preferred lower limit is 30,000, the more preferred upper limit is 60,000, the further preferred lower limit is 35,000, and the further preferred upper limit is 45,000.
[0018] It should be noted that, in this specification, the above-mentioned "weight average molecular weight" is measured by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent, and the value obtained by polystyrene conversion. As a column used when measuring the weight average molecular weight based on polystyrene conversion by GPC, for example, Shodex LF-804 (Showa Denko Co., Ltd.) etc. can be cited.
[0019] The preferred lower limit of the content of the polyisobutylene in 100 parts by weight of the total of the polyisobutylene and the curable resin described later is 10 parts by weight, and the preferred upper limit is 80 parts by weight. By making the content of the polyisobutylene 10 parts by weight or more, the moisture barrier of the obtained resin composition is more excellent. By making the content of the polyisobutylene 80 parts by weight or less, the coating property and adhesion of the obtained resin composition are more excellent. The more preferred lower limit of the content of the polyisobutylene is 20 parts by weight, and the more preferred upper limit is 60 parts by weight.
[0020] The resin composition of the present invention contains a curable resin.
[0021] The curable resin includes carbamate (meth) acrylate. By combining the carbamate (meth) acrylate with fumed silica and containing them in a manner such that they are respectively contained in the amounts described below, the dispersibility of the fumed silica can be improved, and as a result, the resin composition of the present invention can prevent dripping during coating. In addition, by containing the carbamate (meth) acrylate, the resin composition of the present invention has excellent adhesion after being exposed to a high temperature and high humidity environment.
[0022] The urethane (meth)acrylate preferably has a polybutadiene skeleton. The urethane (meth)acrylate has a more excellent effect of improving the dispersibility of fumed silica by having the polybutadiene skeleton.
[0023] The preferred lower limit of the weight average molecular weight of the urethane (meth) acrylate is 2000, and the preferred upper limit is 20,000. By setting the weight average molecular weight of the urethane (meth) acrylate to be within this range, the compatibility with the isobutylene is excellent, and the effect of improving the dispersibility of the fumed silica is more excellent. The more preferred lower limit of the weight average molecular weight of the urethane (meth) acrylate is 5000, and the more preferred upper limit is 10,000.
[0024] Relative to 100 parts by weight of the above-mentioned polyisobutylene, the lower limit of the content of the above-mentioned carbamate (meth) acrylate is 1 part by weight, and the upper limit is 30 parts by weight. By making the content of the above-mentioned carbamate (meth) acrylate more than 1 part by weight, the compatibility with the above-mentioned polyisobutylene is excellent, and the effect of improving the dispersibility of fumed silica is excellent. In addition, the obtained resin composition has excellent adhesion after being exposed to a high temperature and high humidity environment. By making the content of the above-mentioned carbamate (meth) acrylate less than 30 parts by weight, the moisture-proof property of the obtained resin composition is excellent. The preferred lower limit of the content of the above-mentioned carbamate (meth) acrylate is 3 parts by weight, the preferred upper limit is 25 parts by weight, the more preferred lower limit is 5 parts by weight, and the more preferred upper limit is 20 parts by weight.
[0025] From the viewpoint of adhesiveness and the like, the curable resin preferably contains another curable resin other than the urethane (meth)acrylate.
[0026] Examples of the other curable resins include (meth)acrylic compounds not having a urethane bond, epoxy compounds, oxetane compounds, and urethane compounds not having a (meth)acryloyl group. Among them, it is preferred to include the (meth)acrylic compound not having a urethane bond.
[0027] In addition, in this specification, the said "(meth)acrylic acid" means acrylic acid or methacrylic acid, and the said "(meth)acrylic-type compound" means a compound which has a (meth)acryloyl group.
[0028] Examples of the (meth)acrylic compound not having a urethane bond include isobornyl (meth)acrylate, adamantyl (meth)acrylate, methylcyclohexyl (meth)acrylate, norbornyl methyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, cyclodecyl (meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, etc. Among them, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate are preferred.
[0029] As said epoxy compound, a glycidyl ether compound, an alicyclic epoxy compound, etc. are mentioned, for example.
[0030] Examples of the glycidyl ether compound include diethylene glycol diglycidyl ether and the like.
[0031] Examples of the alicyclic epoxy compound include 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate and 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol.
[0032] Examples of the oxetane compound include 1,4-bis{[(3-ethyl-3-oxetanyl)methoxy]methyl}benzene, di[2-(3-oxetanyl)butyl]ether, and 3-ethyl-3-hydroxymethyloxetane.
[0033] As said urethane compound which does not have a (meth)acryloyl group, the reaction product of an isocyanate compound and arbitrary polyol compounds etc. are mentioned, for example.
[0034] As said isocyanate compound, a tolylene diisocyanate compound, a diphenylmethane diisocyanate compound, etc. are mentioned, for example.
[0035] Examples of the tolylene diisocyanate compound include 2,4-tolylene diisocyanate (2,4-TDI), 2,6-tolylene diisocyanate, and a mixture thereof.
[0036] Examples of the diphenylmethane diisocyanate compound include 4,4′-diphenylmethane diisocyanate (4,4′-MDI), 2,4′-diphenylmethane diisocyanate (2,4′-MDI), and a mixture thereof.
[0037] Relative to 100 parts by weight of the polyisobutylene, the preferred lower limit of the content of the other curable resin is 20 parts by weight, and the preferred upper limit is 150 parts by weight. By making the content of the other curable resin within this range, the adhesion and moisture permeability of the obtained resin composition are more excellent. The more preferred lower limit of the content of the other curable resin is 30 parts by weight, the more preferred upper limit is 120 parts by weight, the further preferred lower limit is 40 parts by weight, and the further preferred upper limit is 100 parts by weight.
[0038] The resin composition of the present invention contains a polymerization initiator.
[0039] As the polymerization initiator, a radical polymerization initiator or a cationic polymerization initiator can be used, among which a radical polymerization initiator is preferred.
[0040] As the radical polymerization initiator, a photoradical polymerization initiator or a thermal radical polymerization initiator can be used.
[0041] Examples of the photoradical polymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds.
[0042] Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 1,2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinophenyl)phenyl)-1-butanone, 2,2-dimethoxy-2-phenylacetophenone, bis(2,4,6-trimethylbenzoyl)phenyl 1-(4-(2-hydroxyethoxy)phenyl)-2-hydroxy-2-methyl-1-propane-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, etc. Among them, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one is preferred.
[0043] As said thermal radical polymerization initiator, the thermal radical polymerization initiator containing an azo compound, an organic peroxide, etc. is mentioned, for example.
[0044] Examples of the azo compound include 2,2′-azobis(2,4-dimethylvaleronitrile) and azobisisobutyronitrile.
[0045] Examples of the organic peroxide include benzoyl peroxide, ketone peroxide, peroxyketal, hydrogen peroxide, dialkyl peroxide, peroxyester, diacyl peroxide, and peroxydicarbonate.
[0046] Examples of commercially available products of the thermal radical polymerization initiator include VPE-0201, VPE-0401, VPE-0601, VPS-0501, VPS-1001, and V-501 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0047] Examples of the cationic polymerization initiator include a photocationic polymerization initiator and a thermal cationic polymerization initiator.
[0048] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid by light irradiation, and may be an ionic photoacid generating type or a nonionic photoacid generating type.
[0049] Examples of the anion portion of the ionic photoacid generating type photocationic polymerization initiator include BF4 - PF6 - 、SbF6 - or (BX4) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups) and the like.
[0050] Examples of the ionic photoacid generating type photocationic polymerization initiator include aromatic sulfonium salts, aromatic iodonium salts, aromatic diazonium salts, aromatic ammonium salts, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salts having the anion moiety.
[0051] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, and triphenylsulfonium tetrakis(pentafluorophenyl)borate. Phenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, triarylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, tris(4-(4-acetylphenyl)phenylthio)sulfonium tetrakis(pentafluorophenyl)borate, and the like.
[0052] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate, and the like.
[0053] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.
[0054] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, and the like.
[0055] Examples of the above-mentioned (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.
[0056] Examples of the nonionic photoacid-generating photocationic polymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidesulfonic acid esters.
[0057] Examples of commercially available products of the photocationic polymerization initiator include photocationic polymerization initiators manufactured by MIDORI KAGAKU, photocationic polymerization initiators manufactured by Union Carbide, photocationic polymerization initiators manufactured by ADEKA, photocationic polymerization initiators manufactured by 3M, photocationic polymerization initiators manufactured by BASF, and photocationic polymerization initiators manufactured by Rhodia.
[0058] As the photocationic polymerization initiator manufactured by MIDORI KAGAKU CO., LTD., DTS-200 etc. are mentioned, for example.
[0059] As the photocationic polymerization initiator manufactured by the Union Carbide Co., Ltd., for example, UVI6990, UVI6974, etc. may be mentioned.
[0060] As said ADEKA photocationic polymerization initiator, SP-150, SP-170 etc. are mentioned, for example.
[0061] Examples of the photocationic polymerization initiator manufactured by 3M include FC-508 and FC-512.
[0062] As said BASF company's photocationic polymerization initiator, IRGACURE261, IRGACURE290 etc. are mentioned, for example.
[0063] As the photocationic polymerization initiator manufactured by the Rhodia company, for example, PI2074 etc. can be mentioned.
[0064] As the thermal cationic polymerization initiator, there are: an anion part composed of BF4 - PF6 - 、SbF6 - or (BX4) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups) sulfonium salts, phosphonium salts, ammonium salts, etc. Among them, sulfonium salts and ammonium salts are preferred.
[0065] Examples of the sulfonium salt include triphenylsulfonium tetrafluoroborate and triphenylsulfonium hexafluoroantimonate.
[0066] Examples of the phosphonium salt include ethyltriphenylphosphonium hexafluoroantimonate and tetrabutylphosphonium hexafluoroantimonate.
[0067] Examples of the ammonium salt include dimethylphenyl(4-methoxybenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methoxybenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methylbenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium hexafluorophosphate, and methylphenyldibenzylammonium hexafluorophosphate. hexafluoroantimonate, methylphenyldibenzylammonium tetra(pentafluorophenyl)borate, phenyltribenzylammonium tetra(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetra(pentafluorophenyl)borate, N,N-dimethyl-N-benzylanilinium hexafluoroantimonate, N,N-diethyl-N-benzylanilinium tetrafluoroborate, N,N-dimethyl-N-benzylpyridinium hexafluoroantimonate, N,N-diethyl-N-benzylpyridinium trifluoromethanesulfonic acid, etc.
[0068] As a commercial item among the said thermal cationic polymerization initiators, the thermal cationic polymerization initiator manufactured by Sanshin Chemical Industry Co., Ltd. and the thermal cationic polymerization initiator manufactured by King Industries, Ltd. etc. are mentioned, for example.
[0069] Examples of the thermal cationic polymerization initiator manufactured by Sanshin Chemical Industries, Ltd. include San-Aid SI-60, San-Aid SI-80, San-Aid SI-B3, San-Aid SI-B3A, and San-Aid SI-B4.
[0070] Examples of the thermal cationic polymerization initiator manufactured by King Industries include CXC-1612 and CXC-1821.
[0071] Relative to the total of 100 parts by weight of the polyisobutylene and the curable resin, the preferred lower limit of the content of the polymerization initiator is 0.05 parts by weight, and the preferred upper limit is 10 parts by weight. By making the content of the polymerization initiator more than 0.05 parts by weight, the curability of the resulting resin composition is more excellent. By making the content of the polymerization initiator less than 10 parts by weight, the curing reaction of the resulting resin composition will not become too fast, the workability becomes more excellent, and the cured product can be made more uniform. The more preferred lower limit of the content of the polymerization initiator is 1 part by weight, and the more preferred upper limit is 5 parts by weight.
[0072] The resin composition of the present invention contains fumed silica. The resin composition of the present invention can prevent dripping during coating by combining the fumed silica and the urethane (meth)acrylate in the above-mentioned content and containing them in the content described below.
[0073] The preferred lower limit of the specific surface area of the fumed silica is 80 m 2 / g, the upper limit is preferably 400m 2 By setting the specific surface area of the fumed silica to be within this range, the effect of preventing dripping when applying the obtained resin composition is more excellent. The more preferred lower limit of the specific surface area of the fumed silica is 120 m 2 / g, and the more preferred upper limit is 350m 2 / g, and a further preferred lower limit is 180m 2 / g, and a further preferred upper limit is 330m 2 / g.
[0074] The “specific surface area” can be measured by a BET method using nitrogen gas using a specific surface area measuring device. Examples of the specific surface area measuring device include ASAP-2000 (manufactured by Shimadzu Corporation).
[0075] The preferred lower limit of the average primary particle size of the above-mentioned fumed silica is 2 nm, and the preferred upper limit is 30 nm. By making the average primary particle size of the fumed silica of the present invention within this range, the effect of preventing dripping when applying the obtained resin composition is more excellent. The more preferred lower limit of the average primary particle size of the above-mentioned fumed silica is 5 nm, and the more preferred upper limit is 10 nm.
[0076] The “average primary particle size” can be measured using a dynamic light scattering particle size measuring device, etc. Examples of the dynamic light scattering particle size measuring device include ELSZ-1000S (manufactured by Otsuka Electronics Co., Ltd.).
[0077] Relative to 100 parts by weight of the polyisobutylene, the lower limit of the content of the fumed silica is 1 part by weight and the upper limit is 30 parts by weight. By making the content of the fumed silica more than 1 part by weight, the effect of preventing dripping when applying the obtained resin composition is more excellent. By making the content of the fumed silica less than 30 parts by weight, the adhesion and moisture-proof properties of the obtained resin composition are excellent. The preferred lower limit of the content of the fumed silica is 1.5 parts by weight, the preferred upper limit is 15 parts by weight, the more preferred lower limit is 2 parts by weight, and the more preferred upper limit is 10 parts by weight.
[0078] The ratio of the content of the fumed silica to the content of the urethane (meth)acrylate is preferably 0.1 parts by weight or more and 10 parts by weight or less of the urethane (meth)acrylate per 1 part by weight of the fumed silica.
[0079] The resin composition of the present invention preferably contains a water-absorbing filler. By containing the water-absorbing filler, the resin composition of the present invention has a more excellent moisture permeation prevention property.
[0080] Examples of the water-absorbing filler include oxides of alkaline earth metals, magnesium oxide, and molecular sieves.
[0081] Examples of the alkaline earth metal oxides include calcium oxide, strontium oxide, and barium oxide.
[0082] Among them, from the viewpoint of water absorption, oxides of alkaline earth metals are preferred, and calcium oxide is more preferred.
[0083] These water-absorbing fillers may be used alone or in combination of two or more.
[0084] The preferred lower limit of the content of the water-absorbing filler is 10 parts by weight, and the preferred upper limit is 300 parts by weight, relative to 100 parts by weight of the total of the polyisobutylene and the curable resin. By setting the content of the water-absorbing filler to be within this range, the resulting resin composition has better moisture permeability prevention. The more preferred lower limit of the content of the water-absorbing filler is 30 parts by weight, and the more preferred upper limit is 250 parts by weight.
[0085] The resin composition of the present invention may contain fillers other than the above-mentioned fumed silica and water-absorbing filler for the purpose of improving adhesiveness or the like, within a range not hindering the purpose of the present invention.
[0086] As the other fillers, inorganic fillers and organic fillers can be used.
[0087] Examples of the inorganic filler include silica other than fumed silica, talc, and alumina.
[0088] Examples of the organic filler include polyester microparticles, polyurethane microparticles, vinyl polymer microparticles, acrylic polymer microparticles, etc. Among them, talc is preferred.
[0089] The resin composition of the present invention may contain a thermosetting agent.
[0090] Examples of the thermosetting agent include hydrazide compounds, imidazole derivatives, acid anhydrides, dicyandiamide, guanidine derivatives, modified aliphatic polyamines, and addition products of various amines and epoxy resins.
[0091] Examples of the hydrazide compound include 1,3-bis(hydrazinocarbonylethyl)-5-isopropylhydantoin, sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide.
[0092] Examples of the imidazole derivatives include 1-cyanoethyl-2-phenylimidazole, N-(2-(2-methyl-1-imidazolyl)ethyl)urea, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, N,N'-bis(2-methyl-1-imidazolylethyl)urea, N,N'-(2-methyl-1-imidazolylethyl)-adipic acid diamide, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2-phenyl-4,5-dihydroxymethylimidazole.
[0093] Examples of the acid anhydride include tetrahydrophthalic anhydride and ethylene glycol bis(anhydrotrimellitate).
[0094] These thermosetting agents may be used alone or in combination of two or more.
[0095] Examples of commercially available products of the thermosetting agent include SDH (manufactured by Japan Finechem Co., Ltd.), ADH (manufactured by Otsuka Chemical Co., Ltd.), AJICURE VDH, AJICURE VDH-J, and AJICURE UDH (all manufactured by Ajinomoto Fine-Techno Co., Ltd.).
[0096] Relative to the total of 100 parts by weight of the polyisobutylene and the curable resin, the preferred lower limit of the content of the thermosetting agent is 0.01 parts by weight, and the preferred upper limit is 10 parts by weight. By making the content of the thermosetting agent more than 0.01 parts by weight, the thermosetting property of the obtained resin composition is more excellent. By making the content of the thermosetting agent less than 10 parts by weight, the storage stability of the obtained resin composition is more excellent. The more preferred lower limit of the content of the thermosetting agent is 0.5 parts by weight, the more preferred upper limit is 5 parts by weight, the further preferred lower limit is 1 part by weight, and the further preferred upper limit is 3 parts by weight.
[0097] The resin composition of the present invention may contain a tackifier resin for the purpose of further improving adhesiveness and the like.
[0098] Examples of the tackifier resin include terpene resins, modified terpene resins, coumarone resins, indene resins, and petroleum resins.
[0099] Examples of the modified terpene resin include hydrogenated terpene resins, terpene-phenol copolymer resins, and aromatic modified terpene resins.
[0100] Examples of the petroleum resin include aliphatic petroleum resins, hydrogenated alicyclic petroleum resins, aromatic petroleum resins, aliphatic-aromatic copolymerized petroleum resins, alicyclic petroleum resins, dicyclopentadiene petroleum resins, and hydrogenated products thereof.
[0101] Among them, as the above-mentioned tackifying resin, from the viewpoints of adhesion, moisture permeation resistance, compatibility, etc. of the resin composition, terpene resins, aromatic modified terpene resins, terpene-phenol copolymer resins, hydrogenated alicyclic petroleum resins, aromatic petroleum resins, aliphatic aromatic copolymer petroleum resins, alicyclic petroleum resins are preferred, alicyclic petroleum resins are more preferred, alicyclic saturated hydrocarbon resins, alicyclic unsaturated hydrocarbon resins are further preferred, and cyclohexyl ring-containing saturated hydrocarbon resins and dicyclopentadiene-modified hydrocarbon resins are particularly preferred.
[0102] These tackifier resins may be used alone or in combination of two or more.
[0103] Relative to the total of 100 parts by weight of the polyisobutylene and the curable resin, the preferred lower limit of the content of the tackifying resin is 0.01 parts by weight, and the preferred upper limit is 100 parts by weight. By making the content of the tackifying resin be this range, the effect of improving adhesion can be further exerted while maintaining moisture permeability. The more preferred lower limit of the content of the tackifying resin is 10 parts by weight, and the more preferred upper limit is 40 parts by weight.
[0104] The resin composition of the present invention may contain a sensitizer. The sensitizer has a function of further improving the polymerization initiation efficiency of the polymerization initiator and further promoting the curing reaction of the resin composition of the present invention.
[0105] Examples of the sensitizer include anthracene compounds, thioxanthone compounds, 2,2-dimethoxy-1,2-diphenylethane-1-one, benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4′-bis(dimethylamino)benzophenone, and 4-benzoyl-4′-methyldiphenyl sulfide.
[0106] Examples of the anthracene-based compound include 9,10-dibutoxyanthracene and the like.
[0107] Examples of the thioxanthone-based compound include 2,4-diethylthioxanthone and the like.
[0108] These sensitizers may be used alone or in combination of two or more.
[0109] Relative to the total of 100 parts by weight of the polyisobutylene and the curable resin, the preferred lower limit of the content of the sensitizer is 0.05 parts by weight, and the preferred upper limit is 3 parts by weight. By making the content of the sensitizer more than 0.05 parts by weight, the sensitization effect is further exerted. By making the content of the sensitizer less than 3 parts by weight, the absorption does not become too large, and light can be transmitted to a deep part. The more preferred lower limit of the content of the sensitizer is 0.1 parts by weight, and the more preferred upper limit is 1 part by weight.
[0110] The resin composition of the present invention may contain a stabilizer. By containing the stabilizer, the storage stability of the resin composition of the present invention is further improved.
[0111] Examples of the stabilizer include aromatic amine compounds and 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (Okisil).
[0112] Examples of the aromatic amine compound include benzylamine and aminophenol-type epoxy resins.
[0113] Among them, aromatic amine compounds are preferred, and benzylamine is more preferred.
[0114] These stabilizers may be used alone or in combination of two or more.
[0115] Relative to the total of 100 parts by weight of the polyisobutylene and the curable resin, the preferred lower limit of the content of the stabilizer is 0.001 parts by weight, and the preferred upper limit is 2 parts by weight. By making the content of the stabilizer within this range, the obtained resin composition has better storage stability while maintaining excellent curability. The more preferred lower limit of the content of the stabilizer is 0.005 parts by weight, and the more preferred upper limit is 1 part by weight.
[0116] The resin composition of the present invention may contain a silane coupling agent. The silane coupling agent has a function of improving the adhesion between the resin composition of the present invention and a substrate or the like.
[0117] Examples of the silane coupling agent include 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane. Among them, 3-acryloxypropyltrimethoxysilane is preferred.
[0118] These silane coupling agents may be used alone or in combination of two or more.
[0119] The preferred lower limit of the content of the silane coupling agent is 0.1 parts by weight and the preferred upper limit is 10 parts by weight relative to 100 parts by weight of the total of the polyisobutylene and the curable resin. By making the content of the silane coupling agent within this range, the effect of preventing the excess silane coupling agent from seeping out and improving the adhesion of the obtained resin composition becomes more excellent. The more preferred lower limit of the content of the silane coupling agent is 0.5 parts by weight.
[0120] The resin composition of the present invention may contain a surface modifier within a range that does not hinder the purpose of the present invention. By containing the surface modifier, the flatness of the coating film of the resin composition of the present invention can be improved.
[0121] Examples of the surface modifier include surfactants and leveling agents.
[0122] Examples of the surface modifier include silicone-based, acrylic-based, and fluorine-based surface modifiers.
[0123] Examples of commercially available products of the surface modifier include a surface modifier manufactured by BYK Chemie Japan, a surface modifier manufactured by Kusumoto Chemicals Co., Ltd., and a surface modifier manufactured by AGC Seimi Chemical Co., Ltd.
[0124] Examples of the surface modifier manufactured by BYK Chemie Japan include BYK-300, BYK-302, and BYK-331.
[0125] Examples of the surface modifier manufactured by Kusumoto Chemicals Co., Ltd. include UVX-272.
[0126] Examples of the surface modifier manufactured by AGC SEIMI CHEMICAL include SURFLON S-611.
[0127] The resin composition of the present invention may contain a compound that reacts with an acid generated in the resin composition and / or an ion exchange resin within a range that does not inhibit the purpose of the present invention.
[0128] Examples of the compound that reacts with the generated acid include substances that neutralize with the acid, such as carbonates or hydrogen carbonates of alkali metals, or carbonates or hydrogen carbonates of alkaline earth metals, etc. Specifically, for example, calcium carbonate, calcium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, etc. can be used.
[0129] As the ion exchange resin, any of a cation exchange type, anion exchange type, and a dual ion exchange type can be used, and a cation exchange type or a dual ion exchange type capable of adsorbing chloride ions is particularly suitable.
[0130] The resin composition of the present invention may contain various known additives such as a curing retardant, a reinforcing agent, a softener, a plasticizer, a viscosity modifier, an ultraviolet absorber, and an antioxidant as necessary within a range not hindering the purpose of the present invention.
[0131] From the viewpoint of further suppressing the generation of outgassing, the resin composition of the present invention preferably does not contain a solvent. The resin composition of the present invention can achieve excellent coating properties even if it does not contain a solvent.
[0132] It should be noted that, in the present specification, “containing no solvent” means that the content of the solvent is less than 1000 ppm.
[0133] Examples of a method for producing the resin composition of the present invention include a method of mixing polyisobutylene, a curable resin, a polymerization initiator, fumed silica, and a water-absorbing filler or the like added as required using a mixer.
[0134] Examples of the mixer include a homodisperser, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mill.
[0135] The preferred lower limit of the value obtained by dividing the viscosity measured by using an E-type viscometer at 25°C and 0.5 rpm by the viscosity measured by using an E-type viscometer at 25°C and 5 rpm (hereinafter also referred to as "thixotropic index") of the resin composition of the present invention is 2.0, and the preferred upper limit is 5.0. By making the above-mentioned thixotropic index within this range, the coating property of the resin composition of the present invention is more excellent. The more preferred upper limit of the above-mentioned thixotropic index is 3.5.
[0136] The resin composition of the present invention is preferably used as a peripheral sealant for an organic EL display element for forming a sealing wall around a laminate having an organic light-emitting material layer. The peripheral sealant for an organic EL display element is usually used in combination with an in-plane sealant for an organic EL display element that covers the laminate.
[0137] A peripheral sealant for an organic EL display element using the resin composition of the present invention is also one of the present invention.
[0138] Effects of the Invention
[0139] According to the present invention, it is possible to provide a resin composition having excellent coating properties, adhesion and moisture permeability resistance, and an organic EL display element having excellent display performance can be obtained by using it as a peripheral sealant for an organic EL display element. In addition, according to the present invention, it is possible to provide a peripheral sealant for an organic EL display element formed by using the resin composition. DETAILED DESCRIPTION
[0140] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0141] (Examples 1 to 10, Comparative Examples 1 to 6)
[0142] The materials were stirred and mixed at 2000 rpm for 3 minutes using a stirring mixer according to the mixing ratios listed in Tables 1 and 2 to prepare resin compositions of Examples 1 to 10 and Comparative Examples 1 to 6. ARV-310 (manufactured by THINKY) was used as the stirring mixer.
[0143] For each of the obtained resin compositions, the viscosity at 25° C. and 0.5 rpm and the viscosity at 25° C. and 5 rpm were measured using an E-type viscometer, and the thixotropic index was derived as a value obtained by dividing the viscosity measured at 25° C. and 0.5 rpm by the viscosity measured at 25° C. and 5 rpm. As the E-type viscometer, VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) was used.
[0144] <Evaluation>
[0145] The following evaluations were performed on each of the resin compositions obtained in the Examples and Comparative Examples.
[0146] (1) Coating properties
[0147] Each resin composition obtained in the embodiment and the comparative example is loaded into a syringe, and the discharge adapter of the dispenser is installed, so that the discharge pressure of the dispenser is positive pressure, thus the resin composition is discharged for 10 seconds, and then, it is confirmed that the drip from the front end of the syringe is set to negative pressure for 1 minute. As a syringe, a UV shielding syringe (Musashi Engineering company system) with a capacity of 10mL is used, and as a dispenser, a desktop coating robot SHOTMASTER SX series (Musashi Engineering company system) is used. The situation that no droplets are produced at the front end of the syringe during 1 minute is recorded as "◎", the situation that droplets are produced but not dropped at the front end of the syringe during 1 minute is recorded as "○", the situation that 1 drop of droplets is dropped from the front end of the syringe during 1 minute is recorded as "△", and the situation that more than 2 drops of droplets are dropped from the front end of the syringe during 1 minute is recorded as "×", and coating property is evaluated.
[0148] (2) Adhesion
[0149] For each 10g of the resin composition obtained in the examples and comparative examples, 0.03g of spacer particles with a diameter of 10μm was added and uniformly dispersed using a stirring mixer. Micropearl SP-210 (manufactured by Sekisui Chemical Co., Ltd.) was used as the above-mentioned spacer particles, and ARV-310 (manufactured by THINKY Co., Ltd.) was used as the above-mentioned stirring mixer. After the resin composition dispersed with the spacer particles was applied to the center portion of the glass substrate A, the glass substrate B was crossed and attached in a cross manner, and pressurized to make the thickness uniform. The coating amount of the resin composition dispersed with the spacer particles was adjusted so that the resin composition dispersed with the spacer particles after the thickness became uniform after pressurization became a circle with a diameter of 5.0 to 7.0mm. The above-mentioned glass substrates A and B were obtained by cleaning the surface of a glass with a length of 60mm, a width of 30mm, and a thickness of 5mm with acetone and then drying it. Next, 3000mJ / cm was irradiated using a UV-LED irradiation device. 2 The resin composition was cured by ultraviolet rays with a wavelength of 365 nm, thereby bonding glass substrate A and glass substrate B to obtain a test piece for initial adhesion evaluation. In addition, in the same manner as the test piece for initial adhesion evaluation, glass substrate A and glass substrate B were bonded and then exposed to high temperature and high humidity conditions of 85°C and 85%RH for 500 hours to obtain a test piece for adhesion evaluation after exposure to a high temperature and high humidity environment.
[0150] For each test piece, the glass substrate B was arranged downward, the two ends of the glass substrate A were fixed from below, and the two ends of the glass substrate B were compressed from above at 23°C and a speed of 5mm / min using a precision universal testing machine, thereby measuring the adhesive force between the glass substrate A and the glass substrate B. The compressed part was centered at a position 7.25mm from the two ends of the glass substrate B, and was set to a range of 20mm in length and 5mm in width. As the above-mentioned precision universal testing machine, Autograph AG-Xplus (manufactured by Shimadzu Corporation) was used.
[0151] The adhesive force was defined as the value obtained by dividing the maximum load from the start of compression by a precision universal testing machine until the glass substrate A and the glass substrate B were completely peeled off by the area of the resin composition of the test piece. 2 The above situation is recorded as "◎", which is less than 300N / cm 2 And 250N / cm 2 The above cases are marked as "○", and the pressure less than 250N / cm 2 And 200N / cm 2 If the value is above 200 N / cm, it will be marked as “△”. 2 The case of N was marked as "X", and the initial adhesion and the adhesion after exposure to a high temperature and high humidity environment were evaluated.
[0152] (3) Moisture-proof
[0153] The following Ca-TEST was performed on each of the resin compositions obtained in Examples and Comparative Examples.
[0154] First, 0.03 g of spacer particles with a diameter of 10 μm were added to 10 g of each resin composition obtained in the examples and comparative examples, and the mixture was uniformly dispersed using a stirring mixer. Micropearl SP-210 (manufactured by Sekisui Chemical Co., Ltd.) was used as the spacer particles, and ARV-310 (manufactured by THINKY Co., Ltd.) was used as the stirring mixer. Next, the resin composition in which the spacer particles were dispersed was applied to the surface of a glass substrate.
[0155] Next, a mask having a plurality of 2 mm×2 mm openings was placed on another glass substrate of 30 mm×30 mm size, and Ca was deposited using a vacuum deposition machine. The deposition conditions were as follows: the pressure inside the deposition chamber of the vacuum deposition machine was reduced to 2×10 -3 Pa, Ca The deposition rate of the film The glass substrate on which Ca was vapor-deposited was moved into a glove box controlled at a dew point (above -60°C), and the glass substrate on which the resin composition was applied was bonded to the glass substrate on which Ca was vapor-deposited so that the resin composition was on the vapor-deposited pattern of Ca. After applying pressure to make the thickness of the resin composition layer uniform, the glass substrate was irradiated with 3000 mJ / cm using a UV-LED irradiation device. 2 The resin composition is cured by ultraviolet rays with a wavelength of 365 nm to produce a Ca-TEST substrate.
[0156] The obtained Ca-TEST substrate was exposed to high temperature and high humidity conditions of 85° C. and 85% RH, and the penetration distance of water from the end surface of the glass substrate to the layer containing the cured product of the resin composition was observed based on the disappearance of Ca.
[0157] As a result, the moisture penetration distance when the exposure time to high temperature and high humidity conditions was 1000 hours was recorded as "◎" when it was less than 3.0 mm, "○" when it was 3.0 mm or more and less than 3.5 mm, "△" when it was 3.5 mm or more and less than 4.0 mm, and "×" when it was 4.0 mm or more to evaluate the moisture permeability prevention.
[0158]
[0159]
[0160] Industrial Applicability
[0161] According to the present invention, it is possible to provide a resin composition having excellent coating properties, adhesion and moisture permeability resistance, and an organic EL display element having excellent display performance can be obtained by using it as a peripheral sealant for an organic EL display element. In addition, it is possible to provide a peripheral sealant for an organic EL display element formed by using the resin composition.
Claims
1. A resin composition, characterized in that Contains polyisobutylene, curable resin, polymerization initiator and fumed silica. The weight average molecular weight of the polyisobutylene is 5000 or more and 100,000 or less, The curable resin includes urethane (meth)acrylate and other curable resins other than the urethane (meth)acrylate. The urethane (meth)acrylate has a polybutadiene skeleton, The weight average molecular weight of the urethane (meth)acrylate is 2000 or more and 20,000 or less, The content of the urethane (meth)acrylate is 1 part by weight or more and 30 parts by weight or less relative to 100 parts by weight of the polyisobutylene. The content of the other curable resin other than the urethane (meth)acrylate is 20 parts by weight or more and 150 parts by weight or less based on 100 parts by weight of the polyisobutylene. The curable resin other than the urethane (meth)acrylate includes a (meth)acrylic compound, an epoxy compound, an oxetane compound, or a urethane compound without a (meth)acryloyl group, which has no urethane bond. The content of the fumed silica is 1 part by weight or more and 30 parts by weight or less relative to 100 parts by weight of the polyisobutylene.
2. The resin composition according to claim 1, wherein The curable resin further includes a (meth)acrylic compound having no urethane bond.
3. The resin composition according to claim 1 or 2, wherein The specific surface area of the fumed silica is 80 m 2 / g and above 400m 2 / g or less.
4. The resin composition according to claim 1 or 2, wherein The value obtained by dividing the viscosity measured at 25° C. and 0.5 rpm using an E-type viscometer by the viscosity measured at 25° C. and 5 rpm using an E-type viscometer is 2.0 or more and 5.0 or less. 5 . A peripheral sealant for an organic electroluminescent display element, which is prepared by using the resin composition according to claim 1 , 2 , 3 or 4 .
Citation Information
Patent Citations
Organic electroluminescent panel and method for manufacturing the same
JP2014067598A
Photocurable elastomer composition, seal material, gasket for hard disk drive, hard disk drive and device
CN104968690A
Resin composition for sealing electronic device, and electronic device
CN106062022A
Adhesive composition
CN107636072A
Electronic component-protecting material
JP2013234262A
